MENGGAGAS PESANTREN MASA DEPAN (Kritik Cak Nur atas Pola Pendidikan Tradisional) - Mohammad Salik (El-QUDWAH, 2013)
MENGGAGAS PESANTREN MASA DEPAN (Kritik Cak Nur atas Pola Pendidikan Tradisional)   Oleh : Mohammad Salik UIN Sunan Ampel Surabaya Email: salik_mohamad@yahoo.com Abstract: Nurcholish Madjid is one of the Indonesian Muslim intelectuals who play a significant role as a renewer of Islamic thoughts in Indonesia. Among of his thoughts is about the renewal of education in pesantren (Islamic boarding school). In this case, Nurcholish Madjid critizised some of the weaknesses of Pesantrens. First is about formulating the objectives of Pesantren. In his opinion, Not many pesantrens are able to formulate the aim of education dan set them into clear work plan or program. Second is about the curriculum. In his opinion, the subjects in pesantren are still dominated by religious subjects, even all subjects are only presented in Arabic. Third is about method of teaching. In his opinion, the method of teaching in pesantrens do not emphasize on cognitive aspects. On the contrary, the students are not given the change to express their ideas, this makes the students become passive. Based on these, Nurcholish Madjid proposed some suggestions. First, the teaching of religion in pesantren should be the answer of all life problems, not only partial. Second, pesantren should understand the students` needs and give them the skills which are relevant to the life demand. It seems Nurcholish Madjid make Pondok Modern Gontor as the ideal model of pesantren. Key words: Islamic boarding school, Nurcholish Madjid